Materials and clean processes for sustainable energy and environmental applications: Foreword - Jellali, Salah; Dutournié, Patrick; Jeguirim, Mejdi (Comptes Rendus. Chimie)
Sustainable development strives to fulfill present human needs while safeguarding the ability of future generations to meet their own requirements. Climate change is frequently identified as a major obstacle to realizing this goal. Our current dependence on fossil fuels for energy production is the primary contributor to global climate change. The pivotal solution lies in transitioning to sustainable energy generation by using natural resources like the sun, water, wind, biomass, and others. This shift is fundamental to mitigating climate change and preserving the environment. Utilizing these sources instead of fossil fuels markedly diminishes greenhouse gas emissions, helps in the establishment of a carbon-free global economy. This special edition in Comptes Rendus Chimie (CRC) delves into recent research exploring the role of natural materials, particularly waste, in the production of sustainable energy and environmental protection against both gaseous and liquid pollutants.